2000
DOI: 10.1097/00002030-200009080-00012
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in choosing a primary endpoint that measures durability of virological suppression in an antiretroviral trial

Abstract: A time from randomization endpoint is usually recommended because of its advantages in flexibility and sample size, especially at interim analyses, and for its interpretation for patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…They found that both the choice of definition of the early failure time and the assigned failure time in this time-to-event endpoint definition influenced the results. The authors concluded that a time-from-randomization endpoint should be used that assigns subjects with early virological failure within T weeks a failure time of T weeks (where T is chosen such that >95% of responders are expected to respond by time T) [37].…”
Section: Fixed Time Versus Time To Eventmentioning
confidence: 99%
“…They found that both the choice of definition of the early failure time and the assigned failure time in this time-to-event endpoint definition influenced the results. The authors concluded that a time-from-randomization endpoint should be used that assigns subjects with early virological failure within T weeks a failure time of T weeks (where T is chosen such that >95% of responders are expected to respond by time T) [37].…”
Section: Fixed Time Versus Time To Eventmentioning
confidence: 99%
“…Gilbert et al, (2000) expand on the discussion of virologic failure and consider several competing definitions. Ribaudo et al (2006) discussed design issues in HIV trials, concentrating the discussion of endpoints on further refinements in virologic failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some settings a clear definition of the event of interest is a challenge. An example of such settings include clinical trials evaluating the difference between treatments which are intended to suppress the level of HIV-1 RNA viral load (henceforth viral load) in people infected with HIV (DeGruttola et al, 1998; Gilbert et al, 2000; Ribaudo et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most commonly used endpoint to compare the efficacy of treatment plans is the time to “virologic failure” 37 . The time to virologic failure for patients whose viral load is not suppressed by a predetermined time during the study period is often set to that predetermined time 5,6 or time zero 8 .…”
Section: Introductionmentioning
confidence: 99%